ANALISIS DAYA DUKUNG PONDASI BORED PILE RS. HERMINA BEKASI DENGAN METODE MEYERHOFF DAN REESE AND WRIGHT - Faizal Addin Achmad; Galih Pribadi; Syaiydah Salsabilla (Jurnal Sipil Krisna, 2022)
This final project discussion aims to review one of the important parts in a building planning, namely foundationplanning. This foundation is what supports and holds a load that works on it. A foundation design is said to becorrect if the load transmitted to the soil does not exceed the strength of the soil in question. Soil investigation isvery necessary for planning foundations, especially drill investigations to ensure the depth of hard soil. Theselection of bored pile foundations depends on the surrounding environmental conditions. This study aims to beable to analyze the value of the carrying capacity of the bored pile and to analyze the decrease in the bored pile.General data is obtained from the results of direct observation and observation at the location of the developmentplan. Secondary data is obtained from the contractor or planning consultant as well as the applicable literature,which is used in the analysis. The analytical method used in this final project is to use the Plaxis 3D computerprogram and the manual calculation method to calculate the bearing capacity and settlement of the foundationsupported by various literatures and geotechnical data obtained. Keywords: Pile foundation, pile bearingcapacity, settlement